Consumo de sustancias psicoactivas y los conflictos familiares en los estudiantes de la Unidad Educativa José María Velasco Ibarra, año 2019 - Saavedra Velez, Doris Gabriela (2019)
This research was titled "Consumption of psychoactive substances and family conflicts in the students of the Educational Unit" José María Velasco Ibarra ", Year 2019. Through it, teachers, parents were instructed on the importance of the relationship , psychoactive substances and family conflict, in the adolescence stage. This research work aims to analyze and determine the relationship between the use of psychoactive substances and family conflicts and their consequences on aggressiveness in students, through a bibliographic study, statistical analysis and field study to develop an alternative proposal that contribute to avoid the consumption of psychoactive substances and improve the family conflicts of the students. The theoretical foundation was built through the contents related to the variables defined in the problem. The research was through a mixed approach, of a feasible type, in which deductive and inductive methods were used among others, being a descriptive and bibliographic field research in which observation techniques and surveys applied to teachers, parents of family and high school students who support the results obtained during the entire process of the final investigation report.